The TELAAH KAJIAN SISTEM PENANGGALAN DALAM KITAB AL-HARAKAT AL-SAMAWIYAH WA JAMAWI ILM AL-NUJUM - Hidayah, Nailul Alvi; Izzuddin, Ahmad (UIN ALAUDDIN MAKASSAR, 2023)
Al-Farghani is the author of the book al-harakat al-samawiyah wa jawami ilm al-nujum which contains a summary of astronomy’s sciences. Until now, the book is still being translated into two languages, namely Latin and Arabic. Due to the lack of literature in both English and Indonesian, the author is interested in examining the contents of the book within the scope of Islamic astronomy studies, especially in the first chapter of the book which discusses the calendar system. This study aims to find out how is the study of the calendar system in the book al-harakat al-samawiyah wa jawami ilm al-nujum and how its correlates with modern astronomical knowledge. Library research method with descriptive approach are used in this research. The results of this study indicate that the calendar system contained in the book can be classified into 5 and addopted to 2 systems, namely the Hijri calendar with the lunar system, and Syriac, Roman, Persian and Coptic with a solar system. Each calendar system has a variation in the number of the days and month names. Some of the numbers of days can be correlated with astronomical calculations and some of them are based on culture.